Γ‐Secretase in microglia – implications for neurodegeneration and neuroinflammation. Issue 4 (23rd October 2017) - Walter, Jochen; Kemmerling, Nadja; Wunderlich, Patrick; Glebov, Konstantin
Abstract: γ‐Secretase is an intramembrane cleaving protease involved in the generation of the Alzheimer's disease (AD)‐associated amyloid β peptide (Aβ). γ‐Secretase is ubiquitously expressed in different organs, and also in different cell types of the human brain. Besides the involvement in the proteolytic generation of Aβ from the amyloid precursor protein, γ‐secretase cleaves many additional protein substrates, suggesting pleiotropic functions under physiological and pathophysiological conditions. Microglia exert important functions during brain development and homeostasis in adulthood, and accumulating evidence indicates that microglia and neuroinflammatory processes contribute to the pathogenesis of neurodegenerative diseases. Recent studies demonstrate functional implications of γ‐secretase in microglia, suggesting that alterations in γ‐secretase activity could contribute to AD pathogenesis by modulation of microglia and related neuroinflammatory processes during neurodegeneration. In this review, we discuss the involvement of γ‐secretase in the regulation of microglial functions, and the potential relevance of these processes under physiological and pathophysiological conditions. This article is part of the series "Beyond Amyloid" . Abstract : γ‐Secretase is an intramembrane cleaving protease involved in the generation of the Alzheimer's disease (AD)‐associated amyloid β peptide (Aβ). Besides the role of γ‐secretase in Aβ generation, this protease cleaves many additional protein substrates, suggesting pleiotropic cellular functions. Recent studies indicate functional implications of γ‐secretase in microglia, a cell type critically involved in brain homeostasis and neuroinflammatory processes during neurodegeneration. This review addresses the involvement of γ‐secretase in the regulation of microglia under physiological and pathophysiological conditions. This article is part of the series "Beyond Amyloid" .